Lealdade e trocas relacionais no crédito ao consumidor do varejo hipermercadista - Cohen, Eric David (2004)
In this thesis, we investigate the relationships leading to Satisfaction and Loyalty of credit cardholders issued by Carrefour, the world’s second largest retailer competing neck-to-neck in the Brazilian marketplace with Companhia Brasileira de Distribuição for the customer’s business. A sample of 400 cardholders is analyzed. Card usage data is overlaid with customer data collected through telephone interviews, to support the proposition of measurement models for the Satisfaction, Value, Quality, Attitudinal Loyalty and Behavioral Loyalty constructs. Attitudinal Loyalty occurs when the customer demonstrates his willingness to continue doing business with the company, in spite of more attractive offers from other competitors. Behavioral Loyalty is made evident through traditional metrics such as number of transactions, frequency and monetary value. After construct convergence and discriminant validity criteria are verified, a Loyalty model is implemented using Structural Equation Modeling. An important contribution of this thesis is the use of Survival Analysis for customer attrition modeling. This emerging statistical technique in the areas of Marketing and Administration is used to produce a risk model, which has shown to be effective in the prediction of customer churn, a common problem for issuers and retailers alike. The evidence found in this thesis shows that, for this private label card, purchasing power and access to alternative products plays a major role in customer behavior. Specifically, we have shown that low income customers are more satisfied, more willing to recommend the product to others and increase spending, but are not able to do so because of the limited purchasing power. In contrast, upscale customers are less satisfied, but need additional incentives in order to increase their card spending.